Efeitos de sessões consecutivas de HIIT em marcadores de estresse oxidativo - Rodrigues, Josimar Camacho (2023)
Introduction: High-intensity interval training (HIIT) is characterized by short bouts of high-intensity exercise interspersed with periods of active or passive rest. Several positive results are presented in the scientific literature with HIIT, ranging from improved cardiorespiratory capacity to increased power and muscular endurance. Although HIIT is a training modality well known by athletes and the general population, some information about oxidative stress related to high-intensity training is still unknown. Objective: In this sense, the objective of the present study was to evaluate oxidative damage in an animal model by measuring oxidative stress markers after consecutive sessions of HIIT training in an aquatic environment. Methodology: Wistar rats weighing between 250g - 350g were used. The animals were submitted to swimming exercise, the HIIT protocol consisted of 10 to 14 swimming periods lasting 20 seconds and 10 seconds intervals between each period, performed during 15 consecutive sessions. After 24 hours of the end of the experimental protocol, the animals were properly anesthetized for the collection of samples of blood, muscle (gastrocnemius), liver and heart tissue for analysis. Results: An increase of 305.6% was observed in the production of MDA in the serum of the TG animals (14.49 ± 1.78 nmol EqMDA/ml; p<0.001) in relation to the CG (3.57 ± 1.33 nmol EqMDA/mL) and effect size (ET) was 6.95. As for the muscle tissue, there was a significant increase of 259.2% in the concentration of MDA in the TG (9.61 ± 1.61 nmol EqMDA/mg) in relation to the CG (2.85 ± 0.63 nmol EqMDA/mg ; p<0.001; TE = 5.530. In the liver tissue, there was an increase in 452.6% TG (40.85 ± 7.05 nmol EqMDA/mg; p<0.001), referring to the heart tissue, in the TG (18.06 ± 2.88 nmol EqMDA/mg) HIIT was significantly effective in inducing lipoperoxidation by 215% compared to GC (5.73 ± 2.60 nmol EqMDA/mg; p<0.001; TE = 4.49). The content of the sulfhydryl group evaluated for serum showed a significant reduction of 40% (p<0.001) in GT animals (148.84 ± 24.66 nmol/mL). In muscle tissue, GT (255.75 ± 20.47 nmol/mg) demonstrated a decrease of 44.7% when compared to the CG (462.86 ± 59.64 nmol/mg; p<0.001; TE = 4.65). % of TG (291.92 ± 39.66 nmol/mg) compared to CG (537.07 ± 82.17 nmol/mg; p<0.001; TE = 3.80). significant for the TG (134.83 ± 15.14 nmol/mg) in a percentage of 47.2% when comparing the GC (255.71 ± 37.79 nmol/mg; p<0.001; TE= 4.20). Conclusion: Therefore, it was observed that 15 consecutive sessions in a HIIT swimming protocol promoted oxidative damage in the serum and in the muscular, cardiac and hepatic tissues in Wistar rats, however, further experiments with an animal model are needed, exploring new training protocols in order to observe the behavior of other biomarkers.